The significance of asymptomatic kidney stones as a predictive factor for sepsis in critically ill older adults - (:unkn) unknown (University of Puerto Rico, 2021)
Objective: The objective of this study was to investigate the impact of kidney stones (KSs) on critically ill older adults (CIOA) staying longer than 24 hours in the ICU. Sepsis is one of the leading causes of mortality for ICU patients. KS disease is a well-known risk factor for bacteriuria and urinary tract infection. Methods: A total of 256 CIOA were initially evaluated from April 2017 through February 2019. Patients who had urinary ultrasonography and computed tomography within 12 months prior to ICU admission were included. Patients with an additional urological pathology, under the age of 65 years, and with ICU stays of 24 hours or less were excluded. Consequently, 151 patients were eligible and constituted the study group. These patients were divided into 2 subgroups, according to the presence or absence of KSs. These 2 groups were compared with regard to urine culture (UC) results, presence of urosepsis, and septic shock. Results: The mean age was 80.66 (±7.76) years. There were 18 patients with KSs and 133 without KSs. A total of 71 patients had a positive UC. Repeat UC positivity (p = 0.002) and resistant microorganisms (p = 0.034) were significantly more frequent in the KS group. The incidences of both urosepsis (p<0.001) and septic shock (p<0.001) were also significantly higher in patients with KSs. Conclusion: The presence of KSs in CIOA is frequently associated with urosepsis and septic shock. Large prospective trials are required to evaluate the impact of KSs on the prognosis of patients in the ICU. © 2021, University of Puerto Rico. All rights reserved.
Keywords: Critically ill; Intensive care unit; Kidney stones; Older adults; Sepsis; Urinary tract infection